A longitudinal assessment of ghrelin and bone mineral density with advancing pubertal maturation in adolescent female atlete - Jürimäe, J.; Lätt, E.; Haljaste, K.; Purge, P.; Cicchella, A.; Jürimäe, T. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The aim of the present study was to investigate changes in ghrelin and bone mineral density (BMD) during further biological maturation after onset of puberty in female adolescent swimmers. METHODS: Swimmers (n=17) were tested once a year during a two year study period. At the first year, swimmers were at pubertal stages 2 & 3. Fasting plasma ghrelin, leptin, estradiol, insulin-like growth factor-1 (IGF-I) and BMD of the total body, lumbar spine and femoral neck were measured. RESULTS: Ghrelin did not change during the further pubertal development after onset of puberty. No differences in leptin were also seen during the study period. Estradiol and IGF-I were increased during further pubertal development. Total and lumbar spine BMD increased along with further biological maturation. In contrast, further pubertal development had no effect on femoral neck BMD in adolescent female swimmers. Ghrelin was not related to measured BMD values after adjusting for pubertal status at any measurement time. CONCLUSION: Ghrelin concentration did not change with advancing age and pubertal stage after onset of puberty and had no direct influence on bone mineralisation in adolescent female swimmers.